Analisis Kesalahan Kosakata Bahasa Jepang Tingkat Menengah Pada Pembelajar Dewasa : An Error Analysis of Intermediate Japanese Vocabulary Usage Among Adults Learner - Nurjaman, M Ikhwan F; Rasiban, Linna Meilia; Juangsih, Juju (Undiksha Press, 2025)
Vocabulary mastery is a fundamental aspect of foreign language learning; however, it often becomes a major challenge for learners due to its complex and diverse semantic nature. Previous studies with similar research focus have shown that such difficulties are influenced by various factors, including inadequate teaching methods, first-language interference, and the low frequency of practice activities that support lexical mastery. This study presents the results of an error analysis in Japanese vocabulary acquisition at the intermediate level, equivalent to level N3 on the Japanese Language Proficiency Test (JLPT) scale. The respondents were 25 adult learners aged between 20 and 23 years. Data were collected using a mixed-methods approach and employed three instruments: JLPT N3 based vocabulary test items, the Language Experience and Proficiency Questionnaire (LEAP-Q) developed by Marilyn Logan (2007), which was adapted and modified for this study, and semi structured interviews. The data were analyzed using both qualitative and quantitative methods. The findings indicated that the participants’ average level of Japanese vocabulary mastery was 64%, based on the analysis and calculations discussed. The vocabulary errors identified in this study were categorized into errors and mistakes. It is recommended that learners engage in more intensive reading and composition practice. Future research is advised to involve a larger number of participants with more diverse first-language backgrounds and to utilize more secure testing platforms to minimize the potential for cheating.